2006
DOI: 10.1371/journal.pmed.0030149
|View full text |Cite
|
Sign up to set email alerts
|

Cynomolgus Macaque as an Animal Model for Severe Acute Respiratory Syndrome

Abstract: BackgroundThe emergence of severe acute respiratory syndrome (SARS) in 2002 and 2003 affected global health and caused major economic disruption. Adequate animal models are required to study the underlying pathogenesis of SARS-associated coronavirus (SARS-CoV) infection and to develop effective vaccines and therapeutics. We report the first findings of measurable clinical disease in nonhuman primates (NHPs) infected with SARS-CoV.Methods and FindingsIn order to characterize clinically relevant parameters of SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 49 publications
4
87
0
1
Order By: Relevance
“…Alternatively, the ferrets used in this study were older, and age has been shown to be an important susceptibility factor in the mouse model (Rockx et al, 2007). No other animal, including cynomolgus macaques, has been reported to experience fever, which is the most common sign in human SARS-CoV infection (above 99 %) (Skowronski et al, 2005;Lawler et al, 2006). Thus, ferrets are a good model for SARS-CoV because they are susceptible to infection, support replication in the upper and lower respiratory tracts, develop clinical disease (including fever), shed virus from the upper airway and develop severe lung pathology; this is in agreement with Ferret lungs were analysed on the day of sacrifice and scored for pathology on an increasing scale from normal to multifocal lesions (most severe disease).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the ferrets used in this study were older, and age has been shown to be an important susceptibility factor in the mouse model (Rockx et al, 2007). No other animal, including cynomolgus macaques, has been reported to experience fever, which is the most common sign in human SARS-CoV infection (above 99 %) (Skowronski et al, 2005;Lawler et al, 2006). Thus, ferrets are a good model for SARS-CoV because they are susceptible to infection, support replication in the upper and lower respiratory tracts, develop clinical disease (including fever), shed virus from the upper airway and develop severe lung pathology; this is in agreement with Ferret lungs were analysed on the day of sacrifice and scored for pathology on an increasing scale from normal to multifocal lesions (most severe disease).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, radiographic images of the primate thorax can help elucidate pathological processes intrinsic to the species and help in the study of disease models, or further, for morphometric studies of interest to primatology (Lawler et al 2006, Sharpe et al 2010, Alves 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Animal models described to date include several inbred mouse strains, hamsters, civet cats, ferrets, cats, or nonhuman primates (Fouchier et al, 2003; Glass et al, 2004; Greenough et al, 2005; Hogan et al, 2004; Lawler et al, 2006; Martina et al, 2003; McAuliffe et al, 2004; Qin et al, 2005; Roberts et al, 2005a; 2005b; 2007; Rowe et al, 2004a; Subbarao et al, 2004; ter Meulen et al, 2004; Wu et al, 2005). The timecourse of virus replication in these small animal models is significantly more rapid than that observed in human infections (Roberts et al, 2008) and no model fully reproduces the clinical illness or the pathology observed in humans.…”
Section: Introductionmentioning
confidence: 99%